SIFAT TANAH, EMISI GAS CO2 DAN CH4 DI GULUDAN PADA SISTEM SURJAN LAHAN SULFAT MASAM TIPE LUAPAN B KABUPATEN BARITO KUALA - , Ani Susilawati; , Prof. Dr. Ir. Bambang Hendro Sunarminto, SU., ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the soil fertility states of guludan (ridge) in surjan systems of acid sulfate soil, to find out soil physical as well as chemical properties causing differences in land productivity, and to estimate the quantity of CH4 and CO2 gas emissions from the system. The field study was conducted in July 2010 on the acid sulfate land, located in Karang Indah and Tanjung Harapan villages, Barito Kuala District, South Kalimantan Province. Soil samples ware collected by means of disturbed and undisturbed method at the depth of 0-30 cm and 30-60 cm from the soil surface. CO2 and CH4 gas emissions were measured direcly in the field using Close Chamber technique. The results of the study showed that more intensive land management in the village of Karang Indah has produced a better physical and chemical properties of the ridge soil. The soil fertility in the Karang Indah guludan is higher in comparison with the Tanjung Harapan. The main limiting factor to the ridges productivity of citrus in the Karang Indah and Tanjung Harapan guludan (ridge) is the nutrient retention of low soil pH. Gas emissions of CO2 and CH4 emissions in the Karang Indahâs guludans amounting to 11433.02 mg.m-2.hr-1 and 19.49 mg.m-2.hr-1, which higher than the emissions of CO2 and CH4 emissions in the Tanjung Harapan guludans, that is in the order of 6165.44 mg.m-2.hr-1 and 8.99 mg.m-2.hr-1respectively. The strongest positively relationship between soil physical properties and the emission of CO2 and CH4 gas are through soil temperature, whereas betwen soil chemical properties and emissions of CO2 and CH4 are though the soil pH.